(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The article analyses the concepts of “sovereign” democracy in Russia and “illiberal-Christian” democracy in Hungary, which respectively coincided with the presidencies of Putin and the governments of Orbán. These two experiences show similarities in their conceptualization of illiberal ideas and in the impact they had on institutions and governance. The aim of this work is to investigate Russian and Hungarian illiberal drift, starting from the definition of “sovereign” and “Christian” democracy, focusing on similarities and differences through a comparative perspective.